Analisis bibliometrik perkembangan publikasi authentic assessment pada database scopus 1991 - 2023 - Amin, Khoirul; Ni’mah, Zulfatun; Susanto, Ari (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. Authentic assessment implementation faces challenges due to teachers' limited understanding and the absence of suitable assessment tools, leading to an unfair evaluation of students' cognitive, affective, and psychomotor skills. This study aims to trace the evolution of authentic assessment. Research Methodology. This research employs bibliometric analysis with the keyword